Comparative evaluation of several Dynamics of accumulation of lactic and acetic acids in the process of directed fermentation of white cabbage of the Parus variety - V. V. Kondratenko; N. E. Posokina (Овощи России, 2020)
Relevance and methodology. Today, white cabbage is the most popular type of vegetable raw materials used for fermentation not only in Russia, but also in other countries. To obtain a variety of flavors and shades of flavor, various vegetables (carrots, sweet peppers), fruit (apples, cranberries) and spicy-aromatic additives (cumin, dill seed, etc.) are added to the cabbage during fermentation. During fermentation, the product contains not only the initial components of the raw material (vitamin C, macro-and micronutrients), but also significantly increases the number of lactic acid microorganisms – the main "participants" in the process.One of the main products of the metabolism of lactic acid microorganisms is lactic acid. At a concentration of 0.5%, it begins to inhibit the development of many microorganisms. When reaching a concentration of 1-2% microbiological enzymatic hydrolysis, as a rule, ceases. The accumulation of acetic acid allows us to judge the intensity of the heterofermentative stage of fermentation using strains of lactic acid microorganisms.Results. The L. plantarum + L. casei consortium has shown a synergistic interaction in the accumulation of lactic acid, since the amount of acid produced by the consortium significantly exceeds the amount of acid produced by each strain separately. This point is also noted for the accumulation of acetic acid. In the L. brevis + L. casei consortium, the opposite situation is observed: when using cultures separately, the accumulation of lactic acid occurs to a greater extent than when using two cultures simultaneously. There are no obvious differences between monocultures and the consortium in terms of acetic acid accumulation. In the case of the L. plantarum + L. brevis consortium, we observe a synergistic interaction, with the dominant role in this consortium played by L. plantarum, and the contribution of L. brevis to the accumulation of lactic acid is insignificant. At the same time, the total resulting accumulation of acetic acid is significantly less than the result of each strain separately, which may indicate a negative mutual effect of the participants in the process. Acid degradation of the polysaccharide matrix of cell walls does not occur during the entire fermentation process.